Pedagogic prestidigitation: using magic tricks to enhance educational videos - Richard Wiseman; William Houstoun; Caroline Watt (PeerJ, 2020)
Previous research suggests that magic tricks can be employed within an educational context to enhance attention, engagement, critical thinking and recall. This study builds on this work by examining the impact of incorporating magic tricks into an online educational video. Adult participants (N = 198) completed a need for cognition scale and then watched a video containing either several bespoke card tricks that had been specially devised to help tell the story of the Apollo Moon landings (Magic Video), or an almost identical video that did not contain any magic tricks (Control Video). All participants rated their levels of engagement, absorption and recall. Compared to the Control Video, the Magic Video was rated as significantly more interesting, informative and absorbing. There was no difference between the groups for recall. There was a positive correlation between participants’ need for cognition scores, and the degree to which they found the Magic Video interesting, and were willing to share it with others. The theoretical, methodological and practical implications of these results are discussed, along with recommendations for future work.